EFFECTIVENESS OF VERTIGO REHABILITATION EXERCISE, DIZZINESS AND BALANCE DISORDERS (VDB) IN ELDERLY : NARRATIVE REVIEW - Nirmala Suparmin; Indriani Indriani (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2022)
Vertigo, Dizziness and Balance Disorders (VDB)cause disturbances in the perception of motion or feelings of instability that can affect the ability to see and an unstable gait that causes balance disorders so that immobility can be disturbed, limitations in daily activities, decreased function and can increase the risk of falling. There has been no review of articles that discuss the effectiveness of rehabilitation exercises in patients with Vertigo, Dizziness and Balance Disorders (VDB) in the elderly. To determine the effectiveness of exercise in patients with Vertigo, Dizziness and Balance Disorders (VDB) in the elderly.Narrative review with PICO framework , Identify articles using databases (Google Scholar, Pubmed, and ScienDirect). Selection of articles using PRISMA Flowchart . A total of 434 articles were identified . Articles are limited to 10 years. There were 12 articles that met the inclusion criteria and with the highest prevalence in Brazil 292 population . which states that Vestibular Rehabilitation Therapy (VRT) exercises and Vestibular Rehabilitation with exercise Cawthorne & Cookseycan improve balance .In the practice of Rehabilitation Vestibular Therapy (VRT) and Vestibular Rehabilitation with exercise Cawthorne & Cookseycan reduce symptoms in conditions of balance disorders and produce good results so that it can improve postural stability, self-confidence, can reduce symptoms of dizziness. Functional independence of daily activities can be done at home every day with supervision and doing exercises according to complaints or perceived functional limitationsKeywords: Balance disorders, Cawthorne & Cooksey, Dizziness, Vestibular Rehabilitation Therapy (VRT) and Vertigo